Sideffect GamePlan: Development of an alcohol and other drug serious game for high school students using a systematic and iterative user-centred game development framework. (August 2023) - Nicholas, Joanna; Mills, Brennen; Hansen, Sara; Bright, Stephen J.; Scott, Joseph; Ridout, Imogen; Watson, Jess; Boyd, Heather; Brook, Luke; Hopper, Luke
Abstract: Serious games have shown to be effective in improving motivation to learn, knowledge and retention, thus are being increasingly used for alcohol and other drug (AOD) education. This paper outlines the development of an online AOD serious game for in-class use by Australian secondary school teachers for students in Years 9–10. Adapted from Edwards et al. (2018), the seven-step systematic and iterative user-centred development framework included: (1) Forming an expert multidisciplinary design team, (2) Defining the problem and establishing user preferences, (3) Incorporating the evidence base, (4) Serious game design, (5) Incorporating behavioural and psychological theory, (6) Developing a logic model and investigating causal pathways, and (7) User testing. High school students ( n =  8), health and physical education teachers ( n =  7), and parents ( n =  8) were engaged throughout different stages of the development process to inform development and provide feedback on considerations for promoting engagement, acceptability, and usability of the game amongst both students and teachers. Overall, participants rated game acceptability and usability favourably and would recommend the game for learning about AOD. Constructive feedback and suggestions for improvements from user testing sessions were implemented to form the final version of the game and module. The next step is to test Sideffect GamePlan in a simulated classroom environment before piloting in school settings. Graphical abstract: Image 1 Highlights: A six-lesson alcohol and other drug education package for high school teachers to use in-class with Year 9 and 10 students. Serious game development process outlining conceptual and theoretical approaches. An interactive narrative serious game and in-class activities aligned to Australian health education curriculum. Content focused on alcohol and other drug harm reduction and real-life scenarios. User-centred design approach to promote end-user engagement and adoption.